The neuropsychological profile of delirium vulnerability: A systematic review and meta-analysis. (January 2022) - Ghezzi, Erica S.; Ross, Tyler J.; Sharman, Rhianna; Davis, Daniel; Boord, Monique S.; Thanabalan, Thivina; Thomas, Jessica; Keage, Hannah A.D.
Highlights: Meta-analysis to identify the neuropsychological profile of incident delirium risk. Poor performance across most cognitive domains related to incident delirium. Largest effect sizes for orientation as well as construction and motor performance. Results support theory of whole-brain disintegration underpinning risk for delirium. Abstract: Delirium is a common neurocognitive disorder in hospitalised older adults with substantial negative consequences. Impaired global cognition is a well-established delirium risk factor. However, poor performance on attention tests and higher intra-subject variability may be more sensitive delirium risk factors, given the disorder is characterised by a fluctuating course and attentional deficits. We systematically searched databases (Embase, PsycINFO, MEDLINE) and 44 studies satisfied inclusion criteria. Random-effects meta-analysis models showed poor performance in all cognitive domains except perception was significantly associated with incident delirium. Largest effects were for orientation ( g =-1.20) and construction and motor performance ( g =-0.60). These effects were no longer significant in the subgroup without pre-existing cognitive impairment, where executive functions and verbal functions and language skills were associated with incident delirium. A small, non-significant association between intra-subject variability and incident delirium was found ( g =0.42). Cognitive domain specific tests may be quicker and more sensitive predictors of incident delirium. This pattern of neuropsychological findings supports the proposition that vulnerability for delirium manifests as a dysfunction of whole-brain information integration.